Pengukuran Kualitas Mashlahat dan Madharat dalam PenetapanDispensasi Kawin - Islami, Azim Izzul (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
Eventhough there are differences between hujjah principles of fiqh as theorem, judges at Religious Court (Indonesian Islamic Court) often citingprinciples of fiqh that dismiss mafsadat as preference which called “dar’u al mafasid muqaddamun ala jalb al mashalih” for supporting arguments oflaw as law reasoning in a case request for marriage dispensation. Underage marriage actually confronted between mashlahat and madharat all atonce. Application of principles of fiqh frequently done disproportionate and inappropriate so that it is not in line with the purposes of marriagewhich suppose forming happy and lasting family (household) founded on belief in God Almighty. This research is a normative research with qualitative approach in the form of critical study in applicating mashlahah theory in judge’s decision on marriage dispensation that using principles of fiqh that dismiss mafsadat as preference, but has potential to deviate marriage’s purposes. The result of this research giving description and analysis towards potential’s quality of mashlahat and madharat that will be emerge from underage marriage. A judge must done identification thoroughly towards a child’s readiness to marry, whether there is duress or not and urge reasoning to marry. Comprehensive analytic towards those aspects will generate mashlahat and madharat analysis that measurable so that principles of fiqh that dismiss mafsadat as preference’s application become accurate, proportional and in line with sharia’s goals.